Activation of CDKN2A and Up-regulation of PETN Are Key Features of Sunscreen Usage Versus Light Irradiation: CDKN2A and PETN are key features of sunscreen usage - Robati, Reza M; Moravvej Farshi, Hamideh; Arjmand, Babak; Razzaghi, Zahra; Rezaei, Mitra; Bandarian, Fatemeh; Razi, Farideh; Mansouri, Vahid; Rezaei-Tavirani, Mostafa (Journal of Lasers in Medical Sciences, 2025)
Introduction: Sunscreen plays an unexpected role in protecting the skin against the harmful effects of sunlight. Skin protection against UV rays is highlighted as the main property of sunscreen. The present study investigated the core part of the molecular mechanism of skin protection by sunscreen. Methods: Gene expression changes of the irradiated human skin with sunlight in the presence of sunscreen were mined from the Gene Expression Omnibus (GEO) database and analyzed to find the significantly differentially expressed genes (DEGs). The central DEGs were identified via the protein-protein interaction (PPI) network and searched in skin cancer-related genes in the GeneCards database to find the critical dysregulated genes. The gene expression change of the critical genes was investigated in the Cancer Genome Atlas (TCGA) database. Results: A total of 377 DEGs were determined as the targeted genes. HSPA4, PTEN, CDC42, ERBB2, APP, CDKN2A, PRKACA, PECAM1, and SMAD3 were identified as the critical dysregulated genes. ERBB2, SMAD3, and PRKACA were pointed out as the skin cancer-related genes. Conclusion: In conclusion, the up-regulation of PETN and the activation of CDKN2A were highlighted as the major induced molecular events by sunscreen, which play a role in skin protection.